SOCIAL CAPITAL AND RESILIENCE OF DAWAR ISLAMIC SCHOOL AND ITS ROLES TO SUPPORT SANTRI ALUMNI’S SOCIOECONOMIC INDEPENDENCE - Pargito, Pargito; Arif, Akbarudin; Saptaningtyas, Haryani (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2025)
The role of Islamic boarding schools in Indonesia extends beyond religious education, functioning as agents of socio-economic transformation. This article explores the process of socio-economic independence among graduates of Dawar Islamic Boarding School in Boyolali, Central Java, with particular attention to the dynamics of social capital, graduate networks, and resilience in facing post-boarding challenges. This research employs a Systematic Literature Review (SLR) approach. The SLR analysis draws on national and international publications related to student empowerment, the economics of Islamic boarding schools, and social capital theory to outline the research landscape and reinforce the theoretical foundation. The findings indicate that graduates’ success in achieving independence is shaped not only by the practical skills gained during their education but also by the strength of their social networks, collective norms, and adaptive abilities in accessing economic opportunities. Dawar Islamic Boarding School demonstrates a strategic role in integrating religious instruction with collective work habits, equipping graduates with essential values, competencies, and community-relevant networks. These insights enrich discussions on the contributions of traditional Islamic boarding schools to strengthening civil society and confirm that post-boarding independence results from the interplay of spiritual formation, accumulated social capital, and adaptive strategies in navigating socio-economic realities.